Family relationships in the social network for young male homosexuals - Nadynne Pastoriza dos Santos; Paula Daniella de Abreu; Ednaldo Cavalcante de Araújo; Natália Oliveira de Freitas; Hulda Vale de Araújo; Claudia Benedita dos Santos
ABSTRACT Objective: To evaluate the family relationships in the social network for young male homosexuals. Methods: this is a qualitative, descriptive, exploratory study anchored in the theoretical framework Social Network and including 20 male homosexuals selected by the Snowball technique through semi-structured script interview. The IRaMuTeQ software was analyzed by Similitude Analysis. Results: the primary social network was configured in the elements: 1 - Family affective ties: the center of the social network, 2 - Binding family relationship and religiosity. Final considerations: it was evaluated that the primary social network has been rooted to fragile relationships of socialization and solidarity, and that the social dimension is also rooted on conservatism, sexism/bigotry, and violence. When it comes to address this issue creates the contribution to the visibility of the homosexual youth family dynamics, since it represents the central core and first learning experience that will determine the development and ability to deal with adversities.